Application of the Drazin inverse to the analysis of descriptor fractional discrete-time linear systems with regular pencils - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The Drazin inverse of matrices is applied to find the solutions of the state equations of descriptor fractional discrete-time systems with regular pencils. An equality defining the set of admissible initial conditions for given inputs is derived. The proposed method is illustrated by a numerical example.
Keywords: Drazin inverse; descriptor; fractional systems; discrete-time systems; linear systems